A simplified nonlinear model for bamboo-reinforced concrete beams based on lumped damage mechanics (Fracture and Structural Integrity, 2025)
Bamboo’s renewability may justify bamboo-reinforced concrete (BRC) structures. For practical applications, the accurate description of BRC flexural behaviour is paramount. Lumped damage mechanics is an interesting alternative among some possibilities on nonlinear models since it is based on key concepts of classic fracture and damage mechanics. Therefore, this paper presents a novel lumped damage model for BRC beams. The model’s accuracy is tested with experiments found in the technical literature. Regarding the analysed experiments, the proposed model presents well-fitted results. Finally, the proposed model is feasible for practical applications, even considering structural reliability analysis like Monte Carlo, since it is easy to implement and presents low computational effort.
Keywords: Bamboo-reinforced concrete; nonlinear model; lumped damage mechanics